Akibat Hukum Akta Pelepasan Palsu pada Kasus Relokasi Perluasan Bandara Juanda - Helen Camelia Cahyadi; Lailatul Maghfirah; Fardillah Rizkiansyah (Perspektif Hukum, 2018)
Land disputes are not a new thing that has happened in the long history of law enforcement in this country, often justice becomes overlapping which then ends at the court table, this article will also raise a case of land dispute namely the dispute over the expansion of Juanda airport, this dispute occurred on a 20-hectare plot of land located in Pranti Village, Sedati, Sidoarjo, whose parties are the East Java Pusat Koperasi Karyawan (Puskopkar) center as the land rights holder with PT Gala Bumi Perkasa (GBP), PT Dian Fortuna Erisindo (DFE) with PT Fortuna Harisindo Dian Tama (FHDT), this dispute occurred because of the alleged fake release certificate made by individuals claiming to be members of Puskopar given to PT Gala Bumi Perkasa (GBP), PT Dian Fortuna Erisindo (DFE) with PT Fortuna Harisindo Dian Tama (FHDT) for that legal protection is needed.